FAKTOR-FAKTOR YANG MEMENGARUHI NILAI PERUSAHAAN - Alexander, Abraham; Dewi, Sofia Prima (Jurnal Paradigma Akuntansi, 2024)
This study aims to gain an empirical evidence towards the effect of profitability, capital structure, liquidity, firm size, and dividend policy on firm value. There are 48 samples selected in this study, with a total data of 144 companies engaged in manufacturing that are listed in Indonesia Stock Exchange. This study used a purposive sampling method. The Eviews 12 Student Version used as the selected application to process data in this study. The results shown in this study are profitability, liquidity, and dividend policy do not have a positive effect on firm value, on the other hand capital structure has a positive effect on firm value. Lastly firm size has a negative effect on firm value.